Solid waste management in Bogotá: the role of recycling associations as investigated through SWOT analysis (2017)
In emerging economies, recycling provides an opportunity for cities to increase the lifespan of sanitary landfills, to reduce the costs of solid waste management, to decrease environmental problems from waste treatment by reincorporating waste into the productive cycle and to protect and develop the livelihoods of citizens who work as informal waste pickers. However, few studies have analysed the possibilities of and strategies for integrating the formal and informal sectors in solid waste management for the benefit of both. This integration is the key, especially in developing countries, to understanding how the recycling population can develop a business despite their social and economic limitations. The aim of this study was to perform a strength, weakness, opportunity and threat (SWOT) analysis of three recycling associations in Bogotá with the aim of examining and understanding the recycling situation from the perspective of members of the informal sector in their transition to becoming authorised waste providers. This issue has rarely been studied in the context of developing countries. The data used in the analysis are derived from multiple sources, including a literature review, Bogota’s recycling database, focus group meetings, governmental reports, national laws and regulations and interviews with key stakeholders. The results of this study show that as the primary stakeholders, the formal and informal waste management sectors can identify the internal and external conditions of recycling in Bogotá. Several strategies were designed based on the SWOT analysis. The participation of recycling associations is important in the design and application of waste policy, the consolidation of recycling through an effective business model, promotional programmes for social inclusion and the development of new transformation processes and technologies to valorise recycling materials. In conclusion, recycling associations can become authorised waste providers through a profitable business that increases recycling rates to create a productive process from waste during the generation of new materials and to decrease environmental problems while improving the welfare and living conditions of recyclers. These findings are important for Bogotá to advance and promote recycling as a key strategy for integrated sustainable waste management in the city. © 2016, Springer Science+Business Media Dordrecht.